دور التصور في الربط بين التمثيل الذهني والتمثيل اللغوي في مواضيع ساكنة: دراسة تجريبية - راعي جلال; شمّو أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The purpose of this study is to outline a framework of visuo-spatial static event representations and how conceptual representations (CRs) are mapped onto linguistic representation inventory (LRI) (ii) to detail the role of construal in such a framework (iii) to shed light on schematicity-specificity relation investigating nominals (Ns) and relationals (Rs), and thereby making cross-conceptual and cross-linguistic comparisons between Kurmanji Kurdish and Arabic. The study hypothesizes the existence of both dynamic and meta-dynamic processes. To achieve the objectives, a self-report object-spatial imagery questionnaire applied on a systematic random sample consisted of 15 Syrian Kurds and 15 Arabs; the questionnaire attempted to elicit one or two construals and the dynamic and meta-dynamic processes underlying them. The study suggests that (i) meaning is encyclopedic involving analogization and categorization where the LRs cannot map all subtleties of the CRs (ii) participants profile either Ns or Rs and the percentage of Ns is greater than Rs: Kurdish (N 21>R7) and Arabic (N19>R7) (iii) Figure-ground alignments sound a universal criterion (iv) The LRs are more specific when they have more CRs and vice versa, and that is why they are hierarchical in meaning (v) what is N in Kurdish could be R in Arabic (vi) relation encodings are represented in PPs, VPs, adjectives but the use of active, passive participles, and verbal nouns is Arabic-specific and the use of periphrasis and Pre Per verb form is Kurdish-specific. LRI in Kurdish includes canonical copular clauses (CCCs), existential sentence + present perfect (Pre Per), and periphrastic factitive constructions but LRI in Arabic includes nominal sentences only. Ns are encoded in Nouns, NPs, nominal compounds, *PPs and CCCs in both languages (vii) atemporal Ns and Rs have dynamic relations and/or meta-dynamic relational process in their base. Finally, the study shows that the role of construal in mapping CRs onto LRs is not all-or-nothing, which we may call meta-dynamicity-stativity hypothesis. The meaning of LRs is not a direct pinning down of concepts, but it consists of both the content and the speaker’s construal. يهدف البحث إلى (أ) تأطير تمثيل موضوع ساكن ذو بعد مرئي مكاني وكيفية ارتباط التمثيل الذهني بقائمة محددة من التمثيل اللغوي (ب) شرح دور التصور في هذا الإطار(ت) تسليط الضوء على العلاقة بين المعنى العام التخطيطي (schematicity) والخاص منه(specificity) وذلك بدراسة الاسميات (nominals) والعلاقيات(relationals) مشكلاً بذلك مقارنة ذهنية-لغوية بين اللغتين الكرديّة والعربيّة. ويفترض البحث وجود عمليات ديناميكية وديناميكية تحويلية (meta-dynamic). ولتحقيق الهدف تم تطبيق استبيان التعبير الذاتي عن الصور المكانية على عينة عشوائية تتألف من 15 أكراد سوريين و 15 عرب سوريين تم اختيارهم باتباع الطريقة الممنهجة. حاول الاستبيان استخراج تصور أو تصورين والعمليات الديناميكية والديناميكية التحويلية التي تدعهما. وتوصل البحث بأن (أ) المعنى موسوعي يتضمن عملية مقارنة وتصنيف حيث أن التمثيل اللغوي لايستطيع التعبير عن كل التفاصيل الذهنية(ب) يختار الأشخاص إما الاسميات أو العلاقيات حيث أن نسبة الاسميات أكبر من العلاقيات: الكردية ((N21>R7 والعربية (N19>R7) (ت) يعتبر التمييز بين العنصر والأساس خاصية عامة (ث) إن التمثيل اللغوي يكون أكثر تخصيصاً بالمعنى عندما يتضمن عمليات ذهنية أكثر و العكس صحيح، ولهذا السبب تكون هرمية من حيث المعنى (ج) ما هو اسمي في اللغة الكرديّة قد يكون علائقي في العربيّة (ح) يتم ترميز العلاقة ضمن العلاقيات في العبارات المجرورة و الفعلية و الصفات ولكن استخدام اسم الفاعل واسم المفعول و المصادر خاص باللغة العربيّة، أما استخدام تركيب بإضافة منفصلة(periphrasis) والفعل في صيغة الحاضر التام خاصة بالكردية. القائمة المحددة بالتمثيل اللغوي الكردي يتضمن الجملة البسيطة، الجملة الوجودية + الحاضر التام و التراكيب بإضافة منفصلة، أما في العربية فتتضمن جمل اسمية فقط. يتم ترميز الاسميات في الاسماء و العبارات الاسمية و الاسماء المركبة *وعبارات الجر والعبارات البسيطة في كلا اللغتين (خ) الاسميات والعلاقيات اللازمانية تحوي في مضمونها على علاقات ديناميكية و\أو العملية العلاقية الديناميكية التحويلية. ويمكن تسمية كل هذا الفرضيّة الديناميكيّة التحويليّة السكونيّة(meta-dynamicity-stativity) والتي تظهر أن دور التصور في ربط التمثيل الذهني بالتمثيل اللغوي هي مسألة نسبية. إن معنى التمثيل اللغوي ليس عبارة عن تركيب المفاهيم على الكلمات وإنما تتكون من المعنى و تصور المتكلم لهذا المعنى.